2018
DOI: 10.1159/000495422
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Rated Severity of Illness and Anxiety among Caregivers of Children Born with a Disorder of Sex Development Including Ambiguous Genitalia

Abstract: Background/Aims: Parents of children born with disorders of sex development (DSD) often experience anxiety, but risk factors, including parental perception of the severity of their child’s DSD, have not been examined. We hypothesized that severity of illness (SOI) ratings would relate to parental anxiety, and would be higher for parents of children with a potentially life-threatening DSD (e.g., 21-hydroxylase deficiency). Methods: Eighty-nine parents (Mage = 33.0, 56.2% mothers) of 51 children (M Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Compared with parents of children with other Endocrine conditions, parents of children with DSD reported greater Future Concerns with regards to their child's condition. These results highlight the need for ongoing parental support and effective communication between the multidisciplinary team and families [32] and the provision of early psychological input for parents of young children with DSD [12]. Despite these greater anxieties, fathers of children with DSD reported less stress with regards to attending for Clinic Visits and administering and managing Medication required for their child's condition.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Compared with parents of children with other Endocrine conditions, parents of children with DSD reported greater Future Concerns with regards to their child's condition. These results highlight the need for ongoing parental support and effective communication between the multidisciplinary team and families [32] and the provision of early psychological input for parents of young children with DSD [12]. Despite these greater anxieties, fathers of children with DSD reported less stress with regards to attending for Clinic Visits and administering and managing Medication required for their child's condition.…”
Section: Discussionmentioning
confidence: 85%
“…A significant minority of parents of children with DSD experience symptoms suggestive of post-traumatic stress disorder with accompanying difficulties in communicating news of their child's condition with relatives and close friends, an independent risk factor for emotional distress [8,9]. Yet there is a paucity of studies evaluating the feasibility of routine, longitudinal screening for challenges to positive psychosocial adaptation in the context of usual care [10][11][12]. Such screening would ideally go beyond the heretofore restricted focus on psychosexual differentiation, i.e., gender identity, gender role, and sexual orientation [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Data included in the present study are from the time point each caregiver first completed the stigma measures, which varied from baseline to the fourth annual visit. Portions of data from the larger, multisite study have been reported in previous publications with different aims and hypotheses (Perez et al, 2019, 2021; Roberts, 2020; Sharkey et al, 2018; Suorsa et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…13,14 Algorithms have been proposed to coordinate the prenatal evaluation in these situations, [15][16][17] and much research has centered around the postnatal psychosocial functioning of families with children affected by DSD. [18][19][20][21] However, relatively little attention has been given to the psychosocial implications of the prenatal evaluation. 22,23 While the primary aim of prenatal diagnosis may be to optimize medical care of the infant, an important secondary aim is anticipatory guidance to optimize the family's emotional preparation.…”
Section: Introductionmentioning
confidence: 99%